Gold, lights and burials in the pacific coast of colombian - Peralta Agudelo, Jaime Andrés (Folios, revista de la Facultad de Comunicaciones y Filología, 2010)
The essay here presented is a nonfiction story referred to “burials” that loom on the Pacific Coast. Under this category of representation are known treasures, constituted essentially of gold, which were lost when their original owner died without giving exact information on the location where buried. In turn, they are part of a category of “taxonomic” classification, more generally known as “charms” and they, together with the other manifestations of the association (golden animals, cities of gold, gold deposits, etc...) generally live in aquatic underworld.